Escaping negative moods and concentration problems play bridge roles in the symptom network of problematic smartphone use and depression - Xinyi Wei; Fei An; Chang Liu; Kuiliang Li; Lin Wu; Lei Ren; Xufeng Liu (Frontiers Media S.A., 2023)
BackgroundProblematic smartphone use (PSU) has become an issue of great concern in the age of smartphones. PSU is associated with emotional problems, one of which is depression, as shown by empirical studies. However, previous studies have been limited in that they have focused solely on the total score for symptoms of PSU and depression while ignoring the symptomatic heterogeneity of these two concepts.MethodThis study filled this gap by exploring links between symptoms of PSU and depression among 1,849 university students (59.17% female participants, 17-23 years old). Network analysis was utilized to reveal symptom connections, central symptoms, and bridge symptoms between PSU and depression.Results(1) A total of 17 of 81 symptom connections (about 21%) between PSU and depression existed in the symptom network. For example, "self-control failure" for PSU was positively correlated with "concentration problems" for depression; (2) "recklessly continuing" for PSU and "fatigue" for depression were central symptoms within the PSU symptom network and depression symptom network, respectively; (3) "escaping negative moods" for PSU and "concentration problems" for depression were bridge symptoms. The former was maximumly connected with the depression symptoms and the latter was maximumly connected with the PSU symptoms; and (4) gender had very minimal influence on the network characteristics.ConclusionThe results are in keeping with the central idea of the compensatory internet use theory that excessive smartphone use may be a coping strategy for depressed emotions derived from escaping motivation. Moreover, concentration problems may be a mediator explaining how negative emotions (e.g., depression) cause PSU, which is undefined in current internet use theories. Finally, symptom connections, central symptoms, and bridge symptoms could be potential targets for the prevention and intervention of PSU and depression in young adults.